Physiological factors affecting production of extracellular lipase (LipA) in Acinetobacter calcoaceticus BD413: fatty acid repression of lipA expression and degradation of LipA. - Kok, R G (1996)
The extracellular lipase (LipA) produced by Acinetobacter calcoaceticus BD413 is required for growth of the organism on triolein, since mutant strains that lack an active lipase fail to grow with triolein as the sole carbon source. Surprisingly, extracellular lipase activity and expression of the structural lipase gene (lipA), the latter measured through lacZ as a transcriptional reporter, are extremely low in triolein cultures of LipA+ strains. The explanation for this interesting paradox lies in the effect of fatty acids on the expression of lipA. We found that long-chain fatty acids, especially, strongly repress the expression of lipA, thereby negatively influencing the production of lipase. We propose the involvement of a fatty acyl-responsive DNA-binding protein in regulation of expression of the A. calcoaceticus lipBA operon. The potential biological significance of the observed physiological competition between expression and repression of lipA in the triolein medium is discussed. Activity of the extracellular lipase is also negatively affected by proteolytic degradation, as shown in in vitro stability experiments and by Western blotting (immunoblotting) of concentrated supernatants of stationary-phase cultures. In fact, the relatively high levels of extracellular lipase produced in the early stationary phase in media which contain hexadecane are due only to enhanced stability of the extracellular enzyme under those conditions. The rapid extracellular degradation of LipA of A. calcoaceticus BD413 by an endogenous protease is remarkable and suggests that proteolytic degradation of the enzyme is another important factor in regulating the level of active extracellular lipase.